2020
DOI: 10.1111/psyp.13654
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular function in hypertension: Does high blood pressure make you old?

Abstract: The majority of individuals over an age of 60 have hypertension. Elevated blood pressure and older age are associated with very similar changes in brain structure and function. We review the parallel brain changes associated with increasing age and blood pressure. This review focuses on joint associations of aging and elevated blood pressure with neuropsychological function, regional cerebral blood flow responses to cognitive and metabolic challenges, white matter disruptions, grey matter volume, cortical thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 185 publications
0
16
0
Order By: Relevance
“…One of the most important exacerbating factors is the presence of hypertension, a condition that exists in the majority of individuals over age 60 (Fryar et al., 2017). In this special issue, Jennings et al (2021) present an extensive discussion of the interaction between hypertension and alterations to the cerebrovasculature. There is evidence that arterial stiffening precedes hypertension (Dernellis & Panaretou, 2005; Kaess et al., 2012; Liao et al., 1999; Najjar et al., 2008; Oh, 2018; Oh et al., 2017; Weisbrod et al., 2013).…”
Section: How Does the Cerebrovasculature Change With Age?mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important exacerbating factors is the presence of hypertension, a condition that exists in the majority of individuals over age 60 (Fryar et al., 2017). In this special issue, Jennings et al (2021) present an extensive discussion of the interaction between hypertension and alterations to the cerebrovasculature. There is evidence that arterial stiffening precedes hypertension (Dernellis & Panaretou, 2005; Kaess et al., 2012; Liao et al., 1999; Najjar et al., 2008; Oh, 2018; Oh et al., 2017; Weisbrod et al., 2013).…”
Section: How Does the Cerebrovasculature Change With Age?mentioning
confidence: 99%
“…Somewhat surprisingly, many classes of medications for hypertension work well at reducing blood pressure, but do not treat the factors that caused the hypertension to appear in the first place. Strikingly, there is little evidence that hypertension treatment improves cognitive performance (Iadecola et al., 2016; Jennings et al., 2021). A major theme of this review is that many types of age‐related cerebrovascular dysfunction begin early in life, and are therefore partially preventable or even reversible with appropriate lifestyle adjustments to diet/fasting and exercise (see Aghjayan et al., 2021; Stillman et al., 2021, in this issue; Dong et al., 2020).…”
Section: Synthesis: Trajectories Of Cerebrovascular Impairmentmentioning
confidence: 99%
“…Chronic stress and other factors, such as poor diet and a sedentary life, also contribute to the development of hypertension, which is highly prevalent among middle‐aged and older adults. Jennings et al (2021) review the strong associations between hypertension and the brain and cognitive disruptions that frequently occur with aging. These include volumetric changes in grey matter, white matter dysfunction, as well as blood flow and neuropsychological deficits.…”
mentioning
confidence: 99%
“…Previous studies have shown neurophysiological links between psychological stress and cardiovascular disease risk [ 43 ]. For example, brain blood flow responses to cognitive challenges identify individuals predisposed to hypertension [ 44 ], and activation of the prefrontal cortex during stress influences heart rate variability [ 45 ].…”
Section: Discussionmentioning
confidence: 99%